All-sputtered, flexible, bottom-gate IGZO/Al2O3 bi-layer thin film transistors on PEN fabricated by a fully room temperature process. Issue 28 (7th July 2017) - Zheng, Zeke; Zeng, Yong; Yao, Rihui; Fang, Zhiqiang; Zhang, Hongke; Hu, Shiben; Li, Xiaoqing; Ning, Honglong; Peng, Junbiao; Xie, Weiguang; Lu, Xubing
Abstract : In this work, an innovative all-sputtered bottom-gate thin film transistor (TFT) using an amorphous InGaZnO (IGZO)/Al2 O3 bi-layer channel was fabricated by fully room temperature processes on a flexible PEN substrate. Abstract : In this work, an innovative all-sputtered bottom-gate thin film transistor (TFT) using an amorphous InGaZnO (IGZO)/Al2 O3 bi-layer channel was fabricated by fully room temperature processes on a flexible PEN substrate. A bi-layer channel consisting of 10 nm-thick IGZO and 3 nm-thick Al2 O3 was clearly observed in high resolution TEM images. The chemical structure of IGZO was dependent on different sputtering modes (pulse-DC/DC/RF), which were investigated by XPS measurements. The ultrathin Al2 O3 layer on IGZO showed a significant effect on enhancing the mobility, reducing the off-state current, and improving the gate-bias stability. As a result, the IGZO/Al2 O3 bi-layer TFT eventually exhibited a saturation mobility of 18.5 cm 2 V −1 s −1, an I on / I off ratio of 10 7, an on-state voltage of 1.5 V and a subthreshold swing of 0.27 V decade −1, as well as good stability under NBS/PBS and bending strain. The fabrication of this TFT can be suitably transferred to large-size arrays or paper-like substrates, which is in line with the trend of display development.